A 13-week repeated dose oral toxicity study on a water extract of Artemisia annua in Sprague-Dawley rat - Su-Jin Park; Seong-Hyun Ho; Seon-Hee Kim2; Chanyoung Park; Eun-Young Cho; Ji-Ran You (Journal of Biomedical and Translational Research, 2020)
Artemisia annua (AA) is a well-known as a source of antimalarial drug (artemisinin), which also has been traditionally used as an antipyretic and hemostatic agent in Korea and China. In preclinical effective study, a water extract of Artemisia annua (WEAA) ameliorated weight gain and hepatic lipid accumulation in high-fat diet-fed mice. The plasma levels of triglyceride, AST, and ALT were reduced in the WEAA-treated group. Based on these results, the safety of WEAA as a functional ingredient for liver health was evaluated in this repeated dose oral toxicity study before the clinical trial. Sprague- Dawley (SD) rats were treated by gavage with 20 times (1,000 mg/kg) more than the effective dose for 13 weeks. All rats had survived at the end of the study, and there were no changes indicating obviously abnormal clinical sign and behavior. The treatment of WEAA were also observed no obvious toxicities in the body weights, urine, hematological, serum biochemical, ophthalmic and histopathological examinations. Based on the results of this study, the NOAEL (no-observed-adverse-effect level) of WEAA in SD rats was estimated to be 1,000 mg/kg. In conclusion, WEAA could be used as a safe functional ingredient for the improvement of liver health in individuals with hepatic diseases including nonalcoholic steatohepatitis.